Food security through conservation agriculture (CA) in Zimbabwe: opportunities, prospects and challenges for Gokwe South District: paper presented at a conference held on the 14th-16th July 2015, Elephant Hills Resort, Victoria Fallls, Zimbabwe - Mashango, Gift (Midlands State University, 2016)
Theme: 1st International Research Conference On Driving Socio-Economic Development Through Value Addition And Sustainable Use Of Resources